Anesthetic care of a patient with succinic semi-aldehyde dehydrogenase deficiency - J. Flowers; G. Veneziano; G. Cambier; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal, 2024)
Succinic semialdehyde dehydrogenase (SSADH) defi- ciency is an uncommon autosomal recessive disorder that affects the degradation of gamma-aminobutyric acid (GABA) within the central nervous system (CNS). Clin- ical manifestations generally present during infancy in- cluding hypotonia, developmental delay, cognitive im- pairment, expressive language deficits, and ataxia. Sei- zures are a hallmark of the disorder, being present in ap- proximately half of affected individuals. Given the multi- system involvement of these patients with a high inci- dence of associated seizures, anesthetic care may be re- quired for diagnostic imaging or therapeutic interven- tions. We present a 23-year-old woman with SSADH de- ficiency who required anesthetic care during dental sur- gery. The basic pathophysiology and inheritance of SSADH is presented, clinical manifestations and end-or- gan involvement reviewed, and potential anesthetic im- plications outlined.